Utility of Biochemical Verification of Tobacco Cessation in the Department of Veterans Affairs - Noonan, Devon (Addict Behav, 2012)
Research on the validity of self-report tobacco use has varied by the population studied and has yet to be examined among smokers serviced by the Department of Veterans Affairs (VA). The purpose of this study was to determine the predictors of returning a biochemical urine test and the specificity and sensitivity of self-reported smoking status compared to biochemical verification. This was a sub-analysis of the larger Tobacco Tactics research study, a pre- post- non-randomized control design study to implement and evaluate a smoking cessation intervention in three large VA hospitals. Inpatient smokers completed baseline demographic, health history and tobacco use measures. Patients were sent a follow-up survey at six-months to assess tobacco use and urine cotinine levels. A total of 645 patients returned 6 month surveys of which 578 also returned a urinary cotinine at six months. Multivariate analysis of the predictors of return rate revealed those more likely to return biochemical verification of their smoking status were younger, more likely to be thinking about quitting smoking, have arthritis, and less likely to have heart disease. The sensitivity and specificity of self-report tobacco use was 97% (95% confidence interval=0.95–0.98) and 93% (95% confidence interval=0.84–0.98) respectively. The misclassification rate among self-reported quitters was 21%. The misclassification rate among self-reported smokers was 1%. The sensitivity and specificity of self-report tobacco use was high among veteran smokers, yet among self-report quitters that misclassification rate was high at 21% suggesting that validating self-report tobacco measures is warranted in future studies especially in populations that are prone to misclassification.